A Composite Indicator of Systemic Stress (CISS) for Norway - a Reference Indicator for the Reduction of the Countercyclical Capital Buffer - Yudi Wen (Norges Bank, 2015)
This paper constructs a Composite Indicator of Systemic Stress (CISS) for Norway using a portfolio-theoretic framework as in Hollo\', Kremer and Lo Duca (2012) to facilitate real-time monitoring of the short-term development of systemic stress in the Norwegian financial system. In the aftermath of the global financial crisis, capital requirements are being tightened to make credit institutions more resilient to turmoils in the financial system. As part of the new capital requirements for banks, a counter-cyclical capital buffer has been activated in Norway in the light of Norges Bank's assessment that financial imbalances had been build up over time (Press release 12 December 2013 from the Ministry of Finance). Norges Bank's advice on the level of the buffer is primarily based on four key indicators. However, another type of indicator(s) is needed for the prompt reduction of the buffer in the event of market turbulence and heightened loss prospects for the banking sector, and this paper aims to provide just that.
hdl:11250/2506556
Keywords: 330; GARCH models; financial stress index; financial stability; systemic risk; countercyclical capital buffer